Effectiveness Combination of Electrolysis-Photolysis as Alternative for Drinking Rainwater Treatment - Dila Rahmayanti; Muhammad Taufik Albanjari; Fikry Ardianto; Firra Rosariawari (Nusantara Science and Technology Proceedings)
Rainwater can solve the crisis of clean water and drinking water in Indonesia. The utilization of rainwater as an alternative source of drinking water is one step in encouraging the Sustainable Development Goals (SDGs) program. One technology that can treat rainwater into drinking water is a combination of electrolysis with UV disinfection. Electrocoagulation can reduce physical and chemical pollutant loads, while biological parameters can be reduced by disinfection. Electrocoagulation is the process of clotting and deposition of fine particles in water using electrical energy. UV disinfection is a physical process of removing pathogenic bacteria in water with the help of ultraviolet light. The results of the combination of electrolysis with UV disinfection showed that it could reduce TDS parameters by 69%, turbidity by 72%, color by 18%, hardness by 50%, Fe by 43%, and E-Coli by 100%. So that the water quality has met the drinking water quality standards according to Permenkes No.492, the year 2010, it proves that the combination of electrolysis – UV disinfection is effective in processing rainwater into drinking water.